1976
DOI: 10.1126/science.1857
|View full text |Cite
|
Sign up to set email alerts
|

Specific Effects of Neurotransmitter Antagonists on Ganglion Cells in Rabbit Retina

Abstract: Directionally sensitive ganglion cells in rabbit retina lose their directional sensitivity when picrotoxin, an antagonist of the inhibitory neurotransmitter gamma-aminobutyric acid, is infused into the retinal blood supply. Strychnine, an antagonist of glycine, does not produce this effect. Other receptive field types are affected by strychnine but not picrotoxin. Inhibitory transmitters therefore have specific functions in information processing in the retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(83 citation statements)
references
References 12 publications
4
79
0
Order By: Relevance
“…The relative importance of inhibition in mediating a cell's directional selectivity has been confirmed in many different structures and animals using the same Barlow and Levick paradigm (Ganz and Felder, 1984;Michael, 1965). The role of inhibition also received independent support from rcperimenr, where inhibitory synaptic transmission v.as disrupted pharmacologically with a consequent abolition of directional selectivity (Wyatt andDaw. 1976: Sitlito, 1977).…”
Section: Early Modelsmentioning
confidence: 99%
“…The relative importance of inhibition in mediating a cell's directional selectivity has been confirmed in many different structures and animals using the same Barlow and Levick paradigm (Ganz and Felder, 1984;Michael, 1965). The role of inhibition also received independent support from rcperimenr, where inhibitory synaptic transmission v.as disrupted pharmacologically with a consequent abolition of directional selectivity (Wyatt andDaw. 1976: Sitlito, 1977).…”
Section: Early Modelsmentioning
confidence: 99%
“…The foundation for understanding the cellular mechanisms of direction selectivity in vertebrates was laid by Barlow and Levick (1965), whose extracellular recordings from DSGCs indicated that direction selectivity was mediated primarily by inhibition activated by nulldirection image motion. Strong support for the inhibitory model was provided by subsequent pharmacological experiments, which showed that GABA A -receptor antagonists abolish direction selectivity (Wyatt and Daw, 1976;Ariel and Daw, 1982;Kittila and Massey, 1997). However, these extracellular recording experiments provided no information about whether the inhibition acted directly on the DSGC or presynaptically on the excitatory interneurons.…”
mentioning
confidence: 96%
“…Subsequent studies showed that GABAergic antagonists abolish direction selectivity, suggesting that asymmetric inhibition resulting from null direction stimulus movement plays a crucial role (Barlow and Levick, 1965;Wyatt and Daw, 1976;Caldwell et al, 1978;Ariel and Daw, 1982;Kittila and Massey, 1995). Starburst amacrine cells, interneurons that release both acetylcholine and GABA, synapse onto DS cells and thus have been a favorite candidate for the source of GABAergic inhibition responsible for direction selectivity (Vaney et al, 1989;Famiglietti, 1991Famiglietti, , 1992.…”
Section: Introductionmentioning
confidence: 99%